Paparoscopic resection in a case of normal acth secreting adrenal adenoma - Robledo, Hernán (2001)
A case of Cushing's syndrome due to a normal ACTH secreting adrenal adenoma is discussed. After a successfuly laparoscopic surgical removal, neither clinical nor biochemical abnormalities were noticeable two years later.